Digital Fatigue in Healthcare: The Impact of Technology on Physical and Mental Health - Noor Lusty Putri Setiawati; Juni Purnamasari; Zuriati Zuriati; ⁠Yanita Tri Setiyaningsih; Buntar Handayani; Isnayati Isnayati (Archipel: Journal of Indonesian Interdisciplinary Studies, 2026)
Digitalization has fundamentally transformed healthcare delivery by increasing healthcare professionals' reliance on electronic health records (EHRs), telehealth platforms, mobile communication systems, and other digital technologies. Although these innovations have improved efficiency and continuity of care, prolonged technology exposure has generated growing concerns regarding digital fatigue and its detrimental effects on healthcare workers' physical and psychological well-being. This systematic narrative review aims to synthesize current evidence on the prevalence, underlying mechanisms, and health consequences of digital fatigue among healthcare professionals. A comprehensive literature search was conducted across PubMed, Scopus, Web of Science, PsycINFO, and CINAHL for studies published between 2018 and 2026. Following a rigorous screening process, 25 studies met the inclusion criteria and were included in the final synthesis. The findings indicate that digital fatigue is a widespread and multifaceted occupational health issue characterized by musculoskeletal discomfort, visual strain, sleep disturbances, burnout, anxiety, emotional exhaustion, and reduced cognitive performance. Electronic health records, telehealth platforms, and continuous digital communication emerged as the primary contributors to technostress, with pooled evidence indicating a burnout prevalence of 40.1% among clinicians extensively exposed to EHR systems. Overall, digital fatigue represents a critical challenge for modern healthcare systems, highlighting the urgent need for integrated interventions at the individual, organizational, technological, and policy levels to protect workforce well-being, enhance work performance, and ultimately improve patient safety and quality of care..